TINGKAT KECEMASAN MASYARAKAT SAAT PENCABUTAN GIGI BERDASARKAN USIA, JENIS KELAMIN DAN ASAL DAERAH DENGAN SURVEI ONLINE: DENTAL ANXIETY AMONG PEOPLE DURING TOOTH EXTRACTION BY AGE, GENDER AND AREA OF ORIGIN WITH ONLINE SURVEY - Hendry Rusdy; Beverly (Dentika: Dental Journal, 2015)
Anxiety is a subjective response in a harmless situation or an emotional problem which is caused by human themselves. Anxiety is a major contributor to the reluctance of people to get dental treatment. Dental anxiety was assessed by using Modified Dental Anxiety Scale (MDAS) that was remodified to match during tooth extraction and is widely spread in the internet. A total of 1298 responses were collected two months later. 11-20 years old age group is reported to be moderately anxious with a percentage of 43.51%, while 21-40 years old group and 41-65 years old group were found to be not anxious or slightly anxious with a percentage of 47.04% and 62.65% respectively. A total of 45.42% female were found to be moderately anxious while 52.75% of male were not anxious or slightly anxious. 52.63% of people from Indonesia East Time Zone were reported to be moderately anxious, meanwhile people from Indonesia West Time Zone and Indonesia Central Time Zone were not anxious or slightly anxious with a percentage of 46.05 and 52.41% respectively. The prevalence of dental phobia among people was 4.63%. In conclusion, dental anxiety were found higher in younger ages group, female and people from Indonesia East Time Zone. Kecemasan adalah respons subjektif seseorang bukan pada keadaan berbahaya atau masalah emosional yang penyebabnya adalah diri sendiri. Kecemasan adalah salah satu faktor besar dalam diri manusia yang mempengaruhi seseorang enggan mendapatkan pelayanan kesehatan gigi. Kecemasan dental diperoleh dengan menggunakan Modified Dental Anxiety Scale yangdimodifikasi sesuai dengan keadaan pencabutan gigi dan disebarkan melalui internet. Sejumlah 1298 responden diperoleh dua bulan kemudian. Kelompok usia 11-20 tahun dilaporkan cemas sedang dengan persentase 43,51%, sedangkan kelompok usia 21-40 tahun dan 41-65 tahun dilaporkan tidak cemas atau cemas ringan dengan persentasemasing-masing 47,04% dan 62,65%. Sejumlah 45,42% wanita dilaporkan cemas sedang sedangkan 52,75% laki-laki tidak cemas atau cemas ringan. Sejumlah 52,63% warga negara Indonesia bagian timur dilaporkan cemas sedang, sedangkan warga negara Indonesia bagian barat dan tengah dilaporkan tidak cemas atau sedikit cemas dengan persentase 46,05dan 52,41% masing-masing. Prevalensi fobia atau cemas parah pada masyarakat adalah 4,63%. Sebagai kesimpulan, kecemasan dental ditemukan lebih tinggi pada kelompok usia yang lebih muda, perempuan dan warga negara Indonesia bagian timur.